Parallel Power Electronics Filters in Three-Phase Four-Wire Systems Principle, Control and Design - Wong, Man-Chung; Dai, Ning-Yi; Lam, Chi-Seng (Springer Nature Singapore : Imprint: Springer, 2016)
This book describes parallel power electronic filters for 3-phase 4-wire systems, focusing on the control, design and system operation. It presents the basics of power-electronics techniques applied in power systems as well as the advanced techniques in controlling, implementing and designing parallel power electronics converters. The power-quality compensation has been achieved using active filters and hybrid filters, and circuit models, control principles and operational practice problems have been verified by principle study, simulation and experimental results. The state-of-the-art research findings were mainly developed by a team at the University of Macau. Offering background information and related novel techniques, this book is a valuable resource for electrical engineers and researchers wanting to work on energy saving using power-quality compensators or renewable energy power electronics systems. .